2020
DOI: 10.1371/journal.pbio.3000881
|View full text |Cite
|
Sign up to set email alerts
|

Sequence heterochrony led to a gain of functionality in an immature stage of the central complex: A fly–beetle insight

Abstract: Animal behavior is guided by the brain. Therefore, adaptations of brain structure and function are essential for animal survival, and each species differs in such adaptations. The brain of one individual may even differ between life stages, for instance, as adaptation to the divergent needs of larval and adult life of holometabolous insects. All such differences emerge during development, but the cellular mechanisms behind the diversification of brains between taxa and life stages remain enigmatic. In this stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(69 citation statements)
references
References 89 publications
(201 reference statements)
1
68
0
Order By: Relevance
“…We observed a similar arrangement in the Tribolium embryonic brain (Figure S 3 A-A’’). Recently, we have shown that a subset of embryonically-born columnar neurons express the Retinal homeobox protein (Rx) (Farnworth et al, 2019). Double-staining with anti-GFP and anti-Rx revealed a partial overlap of Rx- and G10011-GFP expressing neurons (Figure S 3 B-B’’’).…”
Section: Resultsmentioning
confidence: 99%
“…We observed a similar arrangement in the Tribolium embryonic brain (Figure S 3 A-A’’). Recently, we have shown that a subset of embryonically-born columnar neurons express the Retinal homeobox protein (Rx) (Farnworth et al, 2019). Double-staining with anti-GFP and anti-Rx revealed a partial overlap of Rx- and G10011-GFP expressing neurons (Figure S 3 B-B’’’).…”
Section: Resultsmentioning
confidence: 99%
“…We asked whether these cells are of embryonic origin and establish the FB primordium (prFB) of the embryonic brain. The prFB is formed by four contra-laterally projecting fiber tracts which emanate from each brain hemisphere and constitute a part of the early commissural system (Farnworth et al, 2020) (schematic illustration in Fig. 3E'').…”
Section: G10011-gfp Positive Neurons Establish the Fb Primordiummentioning
confidence: 99%
“…At late stage NS15 these fibers show the characteristic pattern of defasciculation which initiates the development of the columnar architecture of the FB (Fig. 3G', schematic illustration: G'' and (Farnworth et al, 2020). In Drosophila it has been shown that the contralaterally projecting fibers which constitute the prFB pass through a channel formed by glial membranes (Andrade et al, 2019).…”
Section: G10011-gfp Positive Neurons Establish the Fb Primordiummentioning
confidence: 99%
See 1 more Smart Citation
“…16,500). Further, a number of developmental processes are represented in a more insect-typical way in T. castaneum like for instance segmentation (Tautz et al, 1994), head (Posnien et al, 2010) and leg development, brain development (Farnworth et al, 2019), extraembryonic tissue movements (Panfilio, 2008) and mode of metamorphosis (Snodgrass, 1954). In most cases, the situation in the fly is simplified and streamlined for faster development.…”
Section: Evolutionary Divergence Of Gene Function and Derivededness Omentioning
confidence: 99%